Community Environmental and Tourism Initiatives: A Case From Sri Lankan Perspective - Ratnayake, Konara Mudiyanselage Monju Iraj (2011)
The community tourism approach has become a popular consideration for acquiring active community participation in natural resource management, particularly in mitigating impacts of unsustainable livelihood practices. In Sri Lanka, even though tourism is not new, its potential in delivering benefits to the local community is still a subject of great debate. The problem central to this study evolves from this scenario. The study investigated the community environmental and tourism initiatives (CETIs) in Sri Lanka and their effectiveness in establishing and maintaining relationships between participatory natural resource management efforts and tourism, and to stimulate alternating livelihoods of the marginalised communities. This exploratory study employed qualitative methodology and followed the case study approach which allows the use of mixed-method techniques for the data collection. Presentation and analysis were based on evidence from multiple (six) cases which provided adequate background for critical understanding. The study found that CETIs in Sri Lanka are better at improving awareness in sustainable use of natural resources than at empowering local communities to become self-reliant. The CETIs failed to facilitate community access to benefits of developing tourism in their respective localities, thereby denying them of raised incomes and improved standards of living. Identified barriers of long term success of CETIs include weaknesses in planning processes, lack of supportive policy and institutional framework, generic issues in environmental legislation, inadequate industry linkages, top-down decision-making, lack of domestic capital formation, and limitations in rural labour and shortcomings in capacity development. Some CETIs were found to have collapsed due to weak internal organisation and management, while others survived merely due to their close proximity to existing tourist regions/routes. Inconsistent financial performance due to seasonality of tourism and the overall performance of country's tourism industry were the reasons for the above scenarios. Based on the findings, the study highlighted the pressing need for decisive measures at policy and planning level, and proposed a model of an environment that could be conducive for communities to participate successfully in tourism development in Sri Lanka.